A method for preparing adsorption material for treating arsenic-containing wastewater

By forming an organic compound layer on the sponge iron matrix and modifying graphite alkyne, a new type of adsorption material was prepared, which solved the problem of insufficient removal rate of soluble arsenide in the arsenic-containing sewage in the prior art, and achieved an efficient and highly adaptable adsorption effect.

CN118751210BActive Publication Date: 2025-03-28SHANGHAI MINGCHUN WATER TREATMENT ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411126841.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-28
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

When the existing compound precipitation method treats soluble arsenide in arsenic-containing wastewater, the removal rate is insufficient and the removal of precipitated waste residue is difficult to achieve, making it difficult to meet the needs of industrial applications.

Method used

By forming an NH (CH2COO)2Fe (COC2H5) organic compound layer on the surface of the sponge iron matrix, and introducing octylphenol polyoxyethylene ether composite group on the surface of the graphyne for surface modification, a new type of adsorption material is formed, which is loaded on the sponge iron matrix to improve the adsorption effect of soluble arsenide.

Benefits of technology

The prepared adsorption materials exhibit excellent soluble arsenic adsorption removal performance, wide adaptability, and can effectively remove soluble arsenicides in arsenic-containing wastewater within a wide pH range and high concentration range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118751210B_ABST
    Figure CN118751210B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence: step [1] forming an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of a sponge iron substrate; step [2] introducing an octylphenol polyoxyethylene ether composite group on the surface of graphyne to perform surface modification to obtain modified graphyne; step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer to obtain the adsorbent material. The adsorbent material prepared by the method of the present invention has excellent soluble arsenic adsorption and removal performance, wide pH range and adaptability to soluble arsenide concentration range and other properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorption materials for wastewater treatment, in particular to a method for preparing an adsorption material for treating arsenic-containing wastewater. Background Art

[0002] Due to the transformation of metallic arsenic and its compounds in industries such as smelting, mining, and chemical industry, as well as the widespread use of arsenic compound pesticides in the agricultural field, a large amount of arsenic-containing wastewater is produced. In view of the toxicity of arsenic compounds, the soluble arsenic compounds in these arsenic-containing wastewaters pose a serious threat to ecological environmental safety and human health. After the soluble arsenic compounds in arsenic-containing wastewater are ingested by animals, the arsenic will bind to the sulfhydryl groups of enzyme proteins and the sulfur-containing amino groups of proteins, respectively, interfering with, inhibiting and changing the structure and function of the enzyme, causing acute arsenic poisoning such as thirst, severe abdominal pain, and heart failure, or chronic arsenic poisoning such as liver, nerve and skin lesions and carcinogenesis. When arsenic-containing wastewater containing soluble arsenic compounds is discharged into the soil environment, it will also cause serious harm to plants. Arsenic not only hinders the transport of water in the metabolism process of plants, but also has a destructive effect on the chlorophyll of plants. This toxic effect of arsenic will lead to restricted growth, wilting and death of plants, which has a significant impact on the yield and quality of crops. Therefore, the treatment and control of arsenic-containing wastewater is also of great significance to soil remediation and plant protection.

[0003] At present, one of the main methods for treating soluble arsenides in arsenic-containing wastewater is to use specific compounds to react with soluble arsenides to form precipitates, which are then separated to remove the arsenides from the wastewater. However, the removal rate of the current compound precipitation method for treating soluble arsenides in arsenic-containing wastewater needs to be improved. In addition, the effective removal of precipitated waste residue is also a challenging problem. These problems make it difficult for the current compound precipitation method to meet the industrial application requirements for efficient removal of soluble arsenides in arsenic-containing wastewater. Therefore, further research and technological innovation are needed to improve existing treatment methods and increase removal rates to meet the requirements of environmental protection and health and safety.

[0004] Graphyne has a high specific surface area, a unique acetylenic bond (sp hybridized-C) and a benzene ring (sp2 hybridized-C) structure. Graphyne molecules can interact with arsenic-containing wastewater soluble arsenide σ electrons through van der Waals forces and π-π interactions, thereby adsorbing soluble arsenide. However, its unique structure leads to poor wettability, which inhibits its efficient adsorption of arsenic-containing wastewater soluble arsenide. The present invention forms a group that promotes the wettability of arsenic-containing wastewater on the surface of graphyne, and loads it on a substrate with a large specific surface area and good adsorption of soluble arsenide, forming a new type of arsenic-containing wastewater soluble arsenide adsorption material. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater. The adsorbent material prepared by the method has excellent soluble arsenic adsorption and removal performance, a wide pH range and adaptability to the soluble arsenic concentration range.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] The present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0008] Step [1] forming an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate;

[0009] Step [2] introducing octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne;

[0010] Step [3]: Load the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer to obtain the adsorption material.

[0011] Preferably, the step [1] specifically includes the following operations:

[0012] a1. Adding iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water, mixing to form a base liquid; adding 2-methylpentanal to tetrahydrofuran, mixing to form an additive liquid; adding a certain amount of the additive liquid to the base liquid, mixing to form a synthetic liquid;

[0013] a2. Immerse the sponge iron sample in the synthetic liquid, heat to 60-80°C under closed conditions, keep warm for 6-8 hours, take out the sample and rinse with deionized water, dry at room temperature for 6-12 hours, and obtain a sponge iron with an organic compound layer of NH(CH2COO)2Fe(COC2H5) formed on the surface, which is recorded as intermediate A.

[0014] Preferably, in step a1, the concentration of iminodiacetic acid in the base liquid is 140g / L-180g / L, the concentration of n-butylamine is 80mL / L-120mL / L, the concentration of pentylamine is 50mL / L-90mL / L, and the concentration of sodium ethoxide is 110g / L-150g / L; the concentration of 2-methylpentanal in the additive liquid is 180mL / L-240mL / L; and the volume ratio between the additive liquid and the base liquid in the synthetic liquid is 1-2:3-5.

[0015] Preferably, in step a2, the weight of the sponge iron immersed in each liter of the synthetic liquid is 120-170 g.

[0016] Preferably, the step [2] specifically includes the following operations:

[0017] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H), octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H), Graphene powder is added to deionized water and mixed to form a suspension;

[0018] b2. Using ultrasonic dispersion treatment to keep the graphyne powder fully dispersed in the suspension for 2-5 hours to complete the surface modification of the graphyne to obtain the modified graphene.

[0019] Preferably, the concentration of maleic acid in the suspension is 40 g / L-70 g / L, the concentration of aniline is 10 mL / L-20 mL / L, and the concentration of octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 100mL / L-130mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) is 140mL / L-160mL / L, and the graphyne concentration is 170g / L-220g / L.

[0020] Preferably, the ultrasonic frequency of the ultrasonic dispersion treatment in step b2 is 60 to 90 kHz.

[0021] Preferably, the step [3] specifically includes the following operations:

[0022] c1. Adding pentacarbonyl iron, tromethamine and the modified graphene to deionized water to form a mixed solution, and ultrasonically dispersing the mixture for 1-3 hours to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0023] c2. The intermediate A is immersed in the electrodeposition loading solution and used as the cathode, and the stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 12 to 18 V for 3 to 8 minutes at room temperature to finally obtain the adsorption material.

[0024] Preferably, the concentration of pentacarbonyl iron in the mixed solution in step c1 is 20 mL / L-40 mL / L, the concentration of tromethamine is 70 g / L-90 g / L, and the concentration of modified graphyne is 240 g / L-260 g / L.

[0025] Preferably, in step c2, the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 220-260 g.

[0026] The positive effects of the present invention are as follows: the adsorbent material prepared by the method of the present invention has the following structural characteristics: the NH(CH2COO)2Fe(COC2H5) on the surface of the sponge iron matrix is ​​a complex ion formed by metal iron and iminodiacetate ligands and an organic compound layer (such as Figure 2 As shown), the surface of the organic compound layer is uniformly loaded with octylphenol polyoxyethylene ether (OPE) composite group-modified Graphene (the modified Graphene structure is as shown Figure 3 As shown), octylphenol polyoxyethylene ether complex group is C8H 17 -C6H4-O-(CH2CH2O) 10 H and C8H 17 -C6H4-O-(CH2CH2O)8H octylphenol polyoxyethylene ether group. Based on the above structural characteristics, the multidentate ligand of the organic matter, imidodiacetate, forms a chelate with iron, which is relatively stable in different pH ranges, and the carbon atom electronic structure of the propionyl group in NH(CH2COO)2Fe(COC2H5) has a strong adsorption effect on soluble arsenic compounds; using C8H 17 -C6H4-O-(CH2CH2O) 10 H and C8H 17 -C6H4-O-(CH2CH2O)8H octylphenol polyoxyethylene ether groups are used to modify graphyne, thereby making it have a better wetting effect on arsenic-containing wastewater. The unique acetylene bond of graphyne has a strong interaction with soluble arsenides, which significantly enhances the adsorption effect of the prepared adsorption material on soluble arsenics in arsenic-containing wastewater.

[0027] In summary, the adsorption material prepared according to the present invention has excellent soluble arsenic adsorption and removal performance, wide pH range and adaptability to the concentration range of soluble arsenic compounds and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the adsorption material of the present invention;

[0029] Figure 2 It is a schematic diagram of the structure of NH(CH2COO)2Fe(COC2H5) of the present invention;

[0030] Figure 3 is a schematic structural diagram of the modified graphyne of the present invention;

[0031] Figure 4a It is the soluble trivalent arsenic adsorption removal rate of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under different pH conditions in simulated arsenic-containing wastewater with a concentration of 0.1 mg / L;

[0032] Figure 4b It is the soluble trivalent arsenic adsorption removal rate of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under different pH conditions in simulated arsenic-containing wastewater with a concentration of 0.5 mg / L;

[0033] Figure 5a It is the soluble pentavalent arsenic adsorption removal rate of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under different pH conditions in simulated arsenic-containing wastewater with a concentration of 0.1 mg / L;

[0034] Figure 5b It is the soluble pentavalent arsenic adsorption removal rate of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under different pH conditions in simulated arsenic-containing wastewater with a concentration of 0.5 mg / L. DETAILED DESCRIPTION

[0035] Reference Figure 1 The present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0036] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0037] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 140 g / L-180 g / L, an n-butylamine concentration of 80 mL / L-120 mL / L, a pentylamine concentration of 50 mL / L-90 mL / L and a sodium ethoxide concentration of 110 g / L-150 g / L; add 2-methylvaleraldehyde to tetrahydrofuran to form an additive solution having a 2-methylvaleraldehyde concentration of 180 mL / L-240 mL / L; add the additive solution to the base solution in a volume ratio of 1 to 2:3 to 5 to form a synthetic solution;

[0038] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 120-170g), heated to 60-80°C under closed conditions, kept warm for 6-8 hours, the sample was removed and rinsed with water, dried at room temperature for 6-12 hours, and a sponge iron having an organic compound layer formed on the surface of NH(CH2COO)2Fe(COC2H5) was obtained, which was recorded as intermediate A;

[0039] Step [2] introduces octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, which specifically includes the following operations:

[0040] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10H), octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H), graphene powder was added to deionized water, and mixed to form a mixture with a maleic acid concentration of 40g / L-70g / L, an aniline concentration of 10mL / L-20mL / L, and octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 100mL / L-130mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) with a concentration of 140 mL / L-160 mL / L and a graphyne concentration of 170 g / L-220 g / L;

[0041] b2. Ultrasonic dispersion treatment at a frequency of 60 to 90 kHz is performed to keep the graphene powder fully dispersed in the suspension for 2-5 hours to complete the surface modification of the graphene to obtain the modified graphene;

[0042] Step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer, specifically comprising the following operations:

[0043] c1. Add pentacarbonyl iron, tromethamine, and the modified graphene to deionized water to form a mixed solution having a pentacarbonyl iron concentration of 20 mL / L-40 mL / L, a tromethamine concentration of 70 g / L-90 g / L, and a modified graphene concentration of 240 g / L-260 g / L, and ultrasonically disperse for 1-3 hours to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0044] c2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 220-260 g), and a stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 12 to 18 V for 3 to 8 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with modified graphyne).

[0045] The preferred embodiments of the present invention are described below by way of example.

[0046] Example 1

[0047] Preferred embodiment 1 of the present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0048] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0049] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 170 g / L, an n-butylamine concentration of 90 mL / L, a pentylamine concentration of 60 mL / L and a sodium ethoxide concentration of 130 g / L; add 2-methylvaleraldehyde to tetrahydrofuran to form an additive solution having a 200 mL / L 2-methylvaleraldehyde concentration; add the additive solution to the base solution (the volume ratio of the additive solution to the base solution is 1:5) to form a synthetic solution;

[0050] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 160 g), heated to 65 ° C under closed conditions, kept warm for 7 hours, the sample was removed and rinsed with deionized water, and dried at room temperature for 10 hours to obtain a sponge iron having an organic compound layer formed on the surface of NH (CH2COO) 2Fe (COC2H5), which was recorded as intermediate A;

[0051] Step [2] introduces octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, which specifically includes the following operations:

[0052] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H), octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H), graphene powder was added to deionized water, and mixed to form a mixture with a maleic acid concentration of 50 g / L, an aniline concentration of 12 mL / L, and octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 110mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) with a concentration of 150 mL / L and a graphyne concentration of 190 g / L;

[0053] b2. The Graphene powder was dispersed in the suspension by ultrasonic treatment at a frequency of 80kHz for 3 hours to complete the surface modification of the Graphene to obtain the modified graphene;

[0054] Step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer, specifically comprising the following operations:

[0055] c1. Add pentacarbonyl iron, tromethamine, and the modified graphene to deionized water to form a mixed solution having a pentacarbonyl iron concentration of 30 mL / L, a tromethamine concentration of 80 g / L, and a modified graphene concentration of 250 g / L, and ultrasonically disperse the mixture for 2 hours to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0056] c2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 240 g), and a stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 15 V for 4 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with modified graphyne), which is recorded as Example 1.

[0057] Comparative Example 1

[0058] This comparative example 1 provides a method for preparing an adsorbent material, comprising the following steps performed in sequence:

[0059] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0060] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 150 g / L, an n-butylamine concentration of 90 mL / L, a pentylamine concentration of 60 mL / L and a sodium ethoxide concentration of 120 g / L; add 2-methylvaleraldehyde to tetrahydrofuran to form an additive solution having a 200 mL / L 2-methylvaleraldehyde concentration; add the additive solution to the base solution in a volume ratio of 1:3 to form a synthetic solution;

[0061] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 130 g), heated to 70 ° C under closed conditions, kept warm for 6 hours, the sample was removed and rinsed with deionized water, and dried at room temperature for 7 hours to obtain a sponge iron having an organic compound layer formed on the surface of NH (CH2COO) 2Fe (COC2H5), which was recorded as intermediate A;

[0062] Step [2] loading graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer specifically comprises the following operations:

[0063] b1. Add pentacarbonyl iron, tromethamine and graphene to deionized water to form a mixture of 30 mL / L pentacarbonyl iron, 75 g / L tromethamine and 245 g / L graphene, and ultrasonically disperse for 2 hours to uniformly disperse graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0064] b2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 230 g), and a stainless steel plate is used as the anode. Electrodeposition is carried out at a constant voltage of 13 V for 4 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with graphyne), which is recorded as Comparative Example 1.

[0065] Comparative Example 2

[0066] This comparative example 2 provides a method for preparing an adsorbent material, which specifically includes the following operations:

[0067] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 150 g / L, an n-butylamine concentration of 90 mL / L, a pentylamine concentration of 60 mL / L and a sodium ethoxide concentration of 120 g / L; add 2-methylpentanal to tetrahydrofuran to form an additive solution having a 200 mL / L 2-methylpentanal concentration; add the additive solution to the base solution in a volume ratio of 2:3 to form a synthetic solution;

[0068] a2. Immerse the sponge iron sample in the synthetic liquid (the weight of the sponge iron immersed in each liter of the synthetic liquid is 150 g), heat to 70°C under closed conditions, keep warm for 7 hours, take out the sample and rinse with deionized water, dry at room temperature for 8 hours, and obtain a sponge iron with an organic compound layer of NH(CH2COO)2Fe(COC2H5) formed on the surface, i.e., the adsorption material, which is recorded as Comparative Example 2.

[0069] In order to analyze the adsorption and removal performance of soluble trivalent and pentavalent arsenides in treating arsenic-containing wastewater in Example 1, Comparative Example 1 and Comparative Example 2, arsenic trioxide and disodium hydrogen arsenate were added to deionized water, respectively, and soluble trivalent arsenide simulated arsenic-containing wastewater with arsenic trioxide concentrations of 0.1 mg / L and 0.5 mg / L and soluble pentavalent arsenide simulated arsenic-containing wastewater with disodium hydrogen arsenate concentrations of 0.1 mg / L and 0.5 mg / L were prepared, respectively. The pH values ​​of the prepared trivalent and pentavalent arsenide simulated arsenic-containing wastewater were adjusted with hydrochloric acid and sodium hydroxide to obtain simulated arsenic-containing wastewaters with pH values ​​of 3, 5, 7, 9, and 11. 20g of adsorption material (Example 1, Comparative Example 1, Comparative Example 2) was placed in each liter of simulated arsenic-containing wastewater for soluble arsenic adsorption treatment. The treatment time was 50min. The concentrations of trivalent and pentavalent arsenic in the supernatant of the simulated arsenic-containing wastewater after the adsorption treatment were measured by atomic spectroscopy, and the corresponding trivalent and pentavalent arsenic adsorption removal rates were calculated based on this. The results are as follows: Figure 4a -b, Figure 5a-b. Example 1 shows excellent adsorption and removal performance for soluble trivalent and pentavalent arsenic compounds in simulated arsenic-containing wastewater within the above pH range, and its adsorption and removal rates for trivalent and pentavalent arsenic compounds are both above 85%, while the adsorption and removal performance for soluble trivalent and pentavalent arsenic compounds in simulated arsenic-containing wastewater of Comparative Examples 1 and 2 is significantly lower than that of Example 1, and the maximum soluble arsenic compound does not exceed 55% (this is the removal rate of trivalent arsenic compounds in Comparative Example 1 at a pH value of 3), and the adsorption performance of Comparative Examples 1 and 2 is significantly affected by the pH value. Under alkaline environmental conditions, their adsorption and removal performance for soluble trivalent and pentavalent arsenic compounds in simulated arsenic-containing wastewater deteriorates sharply.

[0070] In summary, the adsorption material prepared according to the present invention has excellent soluble arsenic adsorption and removal performance, wide pH range and adaptability to the concentration range of soluble arsenic compounds and the like.

[0071] To illustrate in further detail, three additional examples are provided below.

[0072] Example 2

[0073] Preferred embodiment 2 of the present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0074] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0075] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 140 g / L, an n-butylamine concentration of 80 mL / L, a pentylamine concentration of 50 mL / L and a sodium ethoxide concentration of 150 g / L; add 2-methylpentanal to tetrahydrofuran to form an additive solution having a 2-methylpentanal concentration of 180 mL / L; add the additive solution to the base solution in a volume ratio of 2:5 to form a synthetic solution;

[0076] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 120 g), heated to 60 ° C under closed conditions, kept warm for 8 hours, the sample was removed and rinsed with deionized water, and dried at room temperature for 6 hours to obtain a sponge iron having an organic compound layer formed on the surface of NH (CH2COO) 2Fe (COC2H5), which was recorded as intermediate A;

[0077] Step [2] introduces octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, which specifically includes the following operations:

[0078] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H17 -C6H4-O-(CH2CH2O) 10 H), octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H), graphene powder was added to deionized water, and mixed to form a mixture with a maleic acid concentration of 40 g / L, an aniline concentration of 10 mL / L, and octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 130mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) with a concentration of 140 mL / L and a graphyne concentration of 170 g / L;

[0079] b2. The Graphene powder was dispersed in the suspension by ultrasonic treatment at a frequency of 60kHz for 2 hours to complete the surface modification of the Graphene to obtain the modified graphene;

[0080] Step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer, specifically comprising the following operations:

[0081] c1. Add pentacarbonyl iron, tromethamine, and the modified graphene to deionized water to form a mixed solution having a pentacarbonyl iron concentration of 20 mL / L, a tromethamine concentration of 70 g / L, and a modified graphene concentration of 260 g / L, and ultrasonically disperse the mixture for 3 hours to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0082] c2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 220 g), and a stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 12 V for 8 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with modified graphyne).

[0083] Example 3

[0084] Preferred embodiment 3 of the present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0085] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0086] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 180 g / L, an n-butylamine concentration of 120 mL / L, a pentylamine concentration of 90 mL / L and a sodium ethoxide concentration of 110 g / L; add 2-methylpentanal to tetrahydrofuran to form an additive solution having a 2-methylpentanal concentration of 240 mL / L; add the additive solution to the base solution in a volume ratio of 1:3 to form a synthetic solution;

[0087] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 170 g), heated to 80 ° C under closed conditions, kept warm for 6 hours, the sample was removed and rinsed with deionized water, and dried at room temperature for 12 hours to obtain a sponge iron having an organic compound layer formed on the surface of NH (CH2COO) 2Fe (COC2H5), which was recorded as intermediate A;

[0088] Step [2] introduces octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, which specifically includes the following operations:

[0089] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H), octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H), graphene powder was added to deionized water, and mixed to form a mixture with a maleic acid concentration of 70 g / L, an aniline concentration of 20 mL / L, and octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 100mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) with a concentration of 160 mL / L and a graphyne concentration of 220 g / L;

[0090] b2. The Graphene powder was dispersed in the suspension by ultrasonic treatment at a frequency of 90kHz for 5 hours to complete the surface modification of the Graphene to obtain the modified graphene;

[0091] Step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer, specifically comprising the following operations:

[0092] c1. Add pentacarbonyl iron, tromethamine, and the modified graphene to deionized water to form a mixed solution having a pentacarbonyl iron concentration of 40 mL / L, a tromethamine concentration of 90 g / L, and a modified graphene concentration of 240 g / L, and ultrasonically disperse for 1 hour to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0093] c2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 260 g), and a stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 18 V for 3 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with modified graphyne).

[0094] Example 4

[0095] Preferred embodiment 4 of the present invention provides a method for preparing an adsorbent material for treating arsenic-containing wastewater, comprising the following steps performed in sequence:

[0096] Step [1] forms an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations:

[0097] a1. Add iminodiacetic acid, n-butylamine, pentylamine and sodium ethoxide to deionized water to form a base solution having an iminodiacetic acid concentration of 160 g / L, an n-butylamine concentration of 100 mL / L, a pentylamine concentration of 70 mL / L and a sodium ethoxide concentration of 130 g / L; add 2-methylpentanal to tetrahydrofuran to form an additive solution having a 2-methylpentanal concentration of 210 mL / L; add the additive solution to the base solution in a volume ratio of 2:3 to form a synthetic solution;

[0098] a2. The sponge iron sample was immersed in the synthetic solution (the weight of the sponge iron immersed in each liter of the synthetic solution was 146 g), heated to 70 ° C under closed conditions, kept warm for 7 hours, the sample was removed and rinsed with deionized water, and dried at room temperature for 10 hours to obtain a sponge iron having an organic compound layer of NH (CH2COO) 2Fe (COC2H5) formed on the surface, which was recorded as intermediate A;

[0099] Step [2] introduces octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, which specifically includes the following operations:

[0100] b1. Maleic acid, aniline, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H), octylphenol polyoxyethylene ether (C8H 17-C6H4-O-(CH2CH2O)8H), graphene powder was added to deionized water, and mixed to form a mixture with a maleic acid concentration of 55 g / L, an aniline concentration of 15 mL / L, and octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O) 10 H) is 120mL / L, octylphenol polyoxyethylene ether (C8H 17 -C6H4-O-(CH2CH2O)8H) with a concentration of 150 mL / L and a graphyne concentration of 195 g / L;

[0101] b2. The Graphene powder was dispersed in the suspension by ultrasonic treatment at a frequency of 75kHz for 4 hours to complete the surface modification of the Graphene to obtain the modified graphene;

[0102] Step [3] loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer, specifically comprising the following operations:

[0103] c1. Add pentacarbonyl iron, tromethamine, and the modified graphene to deionized water to form a mixed solution having a pentacarbonyl iron concentration of 30 mL / L, a tromethamine concentration of 80 g / L, and a modified graphene concentration of 255 g / L, and ultrasonically disperse the mixture for 2 hours to uniformly disperse the modified graphene and pentacarbonyl iron to obtain an electrodeposition loading solution;

[0104] c2. The intermediate A is immersed in the electrodeposition loading liquid and used as the cathode (the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 245 g), and a stainless steel plate is used as the anode. Electrodeposition is performed at a constant voltage of 15 V for 6 minutes at room temperature to finally obtain the adsorption material (sponge iron-based NH(CH2COO)2Fe(COC2H5) layer loaded with modified graphyne).

[0105] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an adsorbent material for treating arsenic-containing wastewater, characterized in that: It contains the following steps in order: Step [1] forming an NH(CH2COO)2Fe(COC2H5) organic compound layer on the surface of the sponge iron substrate, specifically comprising the following operations: a1. The iminodiacetic acid, n-butylamine, pentylamine, sodium ethoxide were added to deionized water and mixed to form a base liquid; 2-methylpentanal was added to tetrahydrofuran and mixed to form an additive liquid; a certain amount of additive liquid was added to the base liquid and mixed to form a synthetic liquid; a2. The sponge iron sample was immersed in the synthetic solution, heated to 60-80 ° C under closed conditions, kept warm for 6-8 hours, the sample was removed and rinsed with water, dried at room temperature for 6-12 hours, and a sponge iron having an organic compound layer formed on the surface of NH (CH2COO) 2Fe (COC2H5) was obtained, which was recorded as intermediate A; Step [2] introducing octylphenol polyoxyethylene ether complex groups on the surface of graphyne to perform surface modification to obtain modified graphyne, specifically comprising the following operations: b1. Maleic acid, aniline, octylphenol polyoxyethylene ether C8H 17 -C6H4-O-(CH2CH2O) 10 H, Octylphenol Polyoxyethylene Ether C8H 17 -C6H4-O-(CH2CH2O)8H, Graphene powder is added to deionized water and mixed to form a suspension; b2. The Graphene powder is dispersed in the suspension by ultrasonic dispersion for 2-5 hours to complete the surface modification of the Graphene to obtain the modified Graphene; Step [3] Loading the obtained modified graphyne on the NH(CH2COO)2Fe(COC2H5) organic compound layer to obtain the adsorption material, specifically comprising the following operations: c1. The pentacarbonyl iron, tromethamine, and the modified Graphene were added to deionized water to form a mixture, and ultrasonically dispersed for 1-3 hours to uniformly disperse the modified Graphene and the pentacarbonyl iron to obtain an electrodeposition loading solution; c2. The intermediate A was immersed in the electrodeposition loading solution and used as the cathode, and the stainless steel plate was used as the anode. Electrodeposition was performed at a constant voltage of 12 to 18 V for 3 to 8 minutes at room temperature to obtain the adsorption material.

2. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: In step a1, the concentration of iminodiacetic acid in the base liquid is 140g / L-180g / L, the concentration of n-butylamine is 80mL / L-120mL / L, the concentration of pentylamine is 50mL / L-90mL / L, and the concentration of sodium ethoxide is 110g / L-150g / L; the concentration of 2-methylpentanal in the additive liquid is 180mL / L-240mL / L; and the volume ratio between the additive liquid and the base liquid in the synthetic liquid is 1-2:3-5.

3. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: In step a2, the weight of the sponge iron immersed in each liter of the synthetic liquid is 120-170g.

4. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: The concentration of maleic acid in the suspension is 40g / L-70g / L, the concentration of aniline is 10mL / L-20mL / L, and the concentration of octylphenol polyoxyethylene ether C8H 17 -C6H4-O-(CH2CH2O) 10 H is 100mL / L-130mL / L, octylphenol polyoxyethylene ether C8H 17 -C6H4-O-(CH2CH2O)8H is 140mL / L-160mL / L, and the graphyne concentration is 170g / L-220g / L.

5. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: The ultrasonic frequency of the ultrasonic dispersion treatment in step b2 is 60~90kHz.

6. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: The concentration of pentacarbonyl iron in the mixed solution in step c1 is 20 mL / L-40 mL / L, the concentration of tromethamine is 70 g / L-90 g / L, and the concentration of modified graphyne is 240 g / L-260 g / L.

7. The method for preparing an adsorbent material for treating arsenic-containing wastewater according to claim 1, characterized in that: In step c2, the weight of the intermediate A immersed in each liter of the electrodeposition loading liquid is 220-260 g.

Citation Information

Patent Citations

  • Preparation method of graphdiyne oxide membrane material for adsorbing and separating uranium

    CN114572960A

  • Preparation method and application of mercury-enriched membrane based on modified graphdiyne oxide

    CN116571214A